2016
DOI: 10.1111/jgs.14573
|View full text |Cite
|
Sign up to set email alerts
|

Continued Use of Warfarin in Veterans with Atrial Fibrillation After Dementia Diagnosis

Abstract: Discontinuing warfarin after a diagnosis of dementia is associated with a significant increase in stroke and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 35 publications
2
30
0
6
Order By: Relevance
“…After diagnosis of dementia, only 16% of patients persisted on warfarin therapy. Using propensity score matching, the protective effect of continuing warfarin persisted in stroke prevention (HR 0.74; 95% CI 0.54-0.996, p 0.047) and mortality (HR 0.72; 95% CI 0.60-0.87, p b 0.001), with no statistically significant decrease in risk of major bleedings (HR 0.78; 95% CI 0.61-1.01, p 0.06), suggesting that warfarin discontinuation after a diagnosis of dementia is associated with a significant increase in stroke and mortality [32].…”
Section: Dementiamentioning
confidence: 96%
See 1 more Smart Citation
“…After diagnosis of dementia, only 16% of patients persisted on warfarin therapy. Using propensity score matching, the protective effect of continuing warfarin persisted in stroke prevention (HR 0.74; 95% CI 0.54-0.996, p 0.047) and mortality (HR 0.72; 95% CI 0.60-0.87, p b 0.001), with no statistically significant decrease in risk of major bleedings (HR 0.78; 95% CI 0.61-1.01, p 0.06), suggesting that warfarin discontinuation after a diagnosis of dementia is associated with a significant increase in stroke and mortality [32].…”
Section: Dementiamentioning
confidence: 96%
“…Moreover, the natural history of individuals with AF taking warfarin who subsequently develop dementia is not well understood. A recent retrospective cohort study in 2572 Veterans ≥ 65 years (73% aged ≥ 75) investigated the effectiveness of warfarin in older patients with AF and dementia [32]. Patients who had been receiving warfarin for nonvalvular AF for at least 6 months and who were newly diagnosed with dementia were followed to assess the incidence of ischemic stroke, major bleedings and overall mortality.…”
Section: Dementiamentioning
confidence: 99%
“…However, in a recent study of veterans (mean age 80 years) with AF, continuation of warfarin after a diagnosis of dementia was associated with a reduction of stroke and mortality, without an increase in major bleeding (66). …”
Section: Tachyarrhythmiasmentioning
confidence: 99%
“…Since a prior stroke represents the strongest predictor of stroke recurrence, all patients who have AF and have had an ischaemic stroke should be anticoagulated, unless an absolute contraindication exists . Of interest, a recent observational study using a propensity score‐matched analysis reported that in individuals with a history of AF and dementia, persistent use of warfarin therapy was uncommon (16%), but was associated with the prevention of stroke [hazard ratio (HR) HR 0.74, 95% CI: 0.54‐0.996; P = .047] and death (HR 0.72, 95% CI: 0.67‐0.87; P < .001) . A recent updated meta‐analysis reported a significant reduction of stroke, stroke or systemic embolism, haemorrhagic stroke, and intracranial bleeding in AF patients with previous stroke or transient ischaemic attack (TIA) receiving NOACs compared with warfarin …”
Section: Atrial Fibrillation and Cognitive Functionmentioning
confidence: 99%